High-temperature-resistant battery box and preparation method thereof

By adding rice husk ash and nitrogen doped TiO2 to the polypropylene composite, the problem of degradation of existing materials under long-term high temperature action is solved, and the composite material with high tensile strength and high temperature resistance is achieved, which extends the battery box Service life.

CN119410069AActive Publication Date: 2025-02-11ZHEJIANG YULONG TECH DEV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510021199.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-07
Publication Date
2025-02-11
Estimated Expiration
2045-01-07

AI Technical Summary

Technical Problem

The existing glass fiber reinforced polypropylene composite materials have weakened interfacial bonding under long-term high temperature action, resulting in a degradation of performance, making it difficult to maintain long-term durability in high-temperature environments.

Method used

By adding rice husk ash and nitrogen-doped TiO2 to the polypropylene composite material and adopting specific preparation methods and process flows, composite materials with high tensile strength and high temperature resistance are formed.

Benefits of technology

The tensile strength and high temperature resistance of the composite material are significantly improved, the service life of the battery box in high temperature environment is extended, and the overall performance of the material is further enhanced through the synergy of rice husk ash and nitrogen-doped TiO2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119410069A_ABST
    Figure CN119410069A_ABST
Patent Text Reader

Abstract

The invention provides a high-temperature-resistant battery box and a preparation method thereof, and belongs to the technical field of composite materials, and the high-temperature-resistant battery box comprises the following components in parts by weight: 65-70 parts of polypropylene, 17-20 parts of glass fiber, 3-4 parts of conductive crystalline flake graphite, 3-5 parts of nitrogen-doped TiO2, 3-5 parts of rice hull ash, 0.6-0.8 part of a lubricant, 11-14 parts of a compatilizer, 0.2-0.6 part of an antioxidant and 0.7-1 part of a light stabilizer. The long-term high temperature resistance of the polypropylene composite material can be improved, so that the service life of the prepared battery box in a high-temperature environment is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of composite materials, and in particular relates to a high temperature resistant battery box and a preparation method thereof. Background Art

[0002] The battery box plays a vital role in the installation of electric vehicle / electric motorcycle batteries. It not only provides physical protection for the battery, but also ensures the stable connection between the battery and the electrical system of the electric vehicle / electric motorcycle. The battery box can provide a solid shell for the battery to prevent the battery from being damaged by external impact, vibration or collision. At the same time, the battery box can also prevent the leakage of battery electrolyte and avoid corrosion to other parts of the vehicle body.

[0003] In the preparation of existing battery boxes, polypropylene (PP) materials are usually used, and other substances are added to obtain other properties. For example, conductive flake graphite is added. By dispersing conductive flake graphite in polypropylene composite materials, a conductive network can be formed, so that the battery box itself has the ability of electromagnetic shielding, and no additional conductive paint or conductive metal sheet bonding process is required, thus saving time and labor costs.

[0004] Another example is adding glass fiber, which has high mechanical strength. When added to polypropylene, these high-strength glass fibers can form a skeleton structure, which bears most of the stress when subjected to external forces, thereby improving the overall tensile strength of the composite material. In addition, glass fiber itself has high thermal stability and can maintain its mechanical properties at high temperatures, thus enhancing the high temperature resistance of polypropylene composite materials.

[0005] However, the short-term performance improvement of glass fiber reinforced polypropylene composites at high temperatures is mainly due to the reinforcing effect of glass fiber. Under long-term high temperature, the interfacial bonding between glass fiber and polypropylene will gradually weaken, resulting in a decrease in the performance of the composite material. Summary of the invention

[0006] In order to solve the problems existing in the background technology, the present invention provides a high temperature resistant battery box and a preparation method thereof, which can improve the long-term high temperature resistance of polypropylene composite materials, thereby improving the service life of the manufactured battery box in a high temperature environment.

[0007] In order to achieve the above-mentioned object, in the first aspect, the present invention provides a high temperature resistant battery box, which comprises the following components by weight: 65-70 parts of polypropylene, 17-20 parts of glass fiber, 3-4 parts of conductive flake graphite, and nitrogen-doped TiO 2 3-5 parts, rice husk ash 3-5 parts, lubricant 0.6-0.8 parts, compatibilizer 11-14 parts, antioxidant 0.2-0.6 parts and light stabilizer 0.7-1 parts.

[0008] Furthermore, the nitrogen-doped TiO 2 The preparation method is as follows:

[0009] B1. At room temperature, add 10 mL of 25% ammonia water to 20 mL of 25% tetrabutyl titanate solution, stir until a precipitate is obtained, then continue stirring for 1.5-2 hours, and then let the precipitate settle for 11-12 hours. The precipitate after settling is washed three times with deionized water to obtain TiO 2 Precursor;

[0010] B2, TiO obtained in B1 2 The precursor was placed in an oven, dried at 60-80°C for 1 hour, and then calcined in a nitrogen atmosphere at 400-420°C for 1 hour to obtain nitrogen-doped TiO 2 .

[0011] Furthermore, in B1, the stirring speed is 500-600 r / min.

[0012] Furthermore, the preparation method of the rice husk ash is as follows:

[0013] C1. Immerse the rice husk in an acid solution with a mass fraction of 2-2.5% for 1-2 hours, filter out, wash with water until neutral, and dry naturally to obtain acid-soaked rice husk;

[0014] C2. Place the acid-soaked rice husk obtained in C1 into a crucible, and then into a muffle furnace, calcine at 600-640°C for 25-30 minutes, take out, and naturally cool to room temperature to obtain rice husk ash.

[0015] Furthermore, the lubricant is calcium stearate or polyethylene wax.

[0016] Furthermore, the compatibilizer is a polylactic acid grafted cellulose acetate copolymer.

[0017] Furthermore, the light stabilizer is 2-(2-hydroxy-3,5-dibutyl-tert-phenyl)-5-chlorobenzotriazole.

[0018] Furthermore, the antioxidant is bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite.

[0019] In a second aspect, the present invention provides a method for preparing the above-mentioned high temperature resistant battery box, comprising the following steps:

[0020] S1, polypropylene, glass fiber, conductive flake graphite, nitrogen-doped TiO 2 , rice husk ash, lubricant, compatibilizer, antioxidant and light stabilizer are added into a mixer at a speed of 350-400 r / min, and stirred for 5-8 minutes to obtain a mixture;

[0021] S2, the mixed material obtained in S1 was vacuum dried at a temperature of 70°C and an absolute pressure of 0.02MPa for 2h, and then added into a twin-screw extruder for melt extrusion granulation, wherein the temperature of the first zone of the twin-screw extruder was 175°C, the temperature of the second zone was 185°C, the temperature of the third zone was 180°C, the temperature of the fourth zone was 190°C, the temperature of the fifth zone was 170°C, the head temperature was 160°C, and the main engine speed was 380rpm, to obtain a composite material;

[0022] S3. The composite material obtained in S2 is injection molded at 210-230°C, then cooled to room temperature, and demolded to obtain a battery box.

[0023] This application has the following beneficial effects:

[0024] 1. In the preparation of the high temperature resistant battery box of the present invention, the addition of the raw material component rice husk ash can improve the tensile strength and high temperature resistance of the composite material / battery box; nitrogen-doped TiO 2 The addition of can also improve the tensile strength and high temperature resistance of the composite material / battery box; and rice husk ash and nitrogen-doped TiO 2 A synergistic effect can be produced to synergistically improve the tensile strength and high temperature resistance of the composite material / battery box.

[0025] 2. In the preparation of rice husk ash, the rice husk is acid-soaked and then calcined at a constant temperature to form ash, presenting a dense interlaced flaky structure with a raised center, with a certain degree of roughness and irregular shape, which can reduce the mutual attraction and aggregation between particles, avoid agglomeration, and facilitate uniform dispersion. The bimodal porosity in the rice husk ash particles improves the interface anchoring effect through capillary action. This interface anchoring effect not only enhances the bonding force between the rice husk ash and the polypropylene matrix, but also promotes the interface compatibility between the glass fiber and the matrix. The nanoscale pores on the surface of the rice husk ash can provide more active sites, which is conducive to the embedding and fixation of the glass fiber, thereby forming a more solid interface layer. This solid interface layer can not only effectively transfer stress and improve the overall mechanical properties (tensile strength) of the composite material, but also resist the weakening trend of bonding under the influence of high temperature, and improve the high temperature resistance of the composite material.

[0026] 3. Nitrogen-doped TiO 2 In the preparation of TiO, the introduction of nitrogen can change the 2The electronic structure and surface properties of the glass fiber can be modified to obtain more active sites and mesoporous structures. These active sites can chemically bond or physically adsorb with the functional groups on the surface of the glass fiber (such as hydroxyl, carboxyl, etc.) and the polypropylene molecular chain, thereby acting as a "bridge" to improve the bonding strength between the glass fiber and the polypropylene; and these mesoporous structures can provide additional space for the glass fiber and the polypropylene, allowing them to form a more compact arrangement inside the material, and the mesoporous structure can also accommodate and fix the glass fiber and the polypropylene to prevent them from relative sliding or detaching when heated / stressed, thereby further improving the tensile strength and high temperature resistance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 , a comparative trend chart of tensile strength test data of composite materials obtained from Examples 1 to 7 of the present invention and Comparative Examples 1 to 5;

[0028] Figure 2 , a comparative trend chart of the tensile strength retention rate of the composite materials prepared in Examples 1 to 7 of the present invention and Comparative Examples 1 to 5 after high-temperature treatment at 120°C for 7 days. DETAILED DESCRIPTION

[0029] The present application is further described in detail below with reference to the embodiments.

[0030] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0031] Example 1: (1) Preparation of nitrogen-doped TiO 2 , and its preparation method is as follows:

[0032] B1. At room temperature, 10 mL of 25% ammonia water was added dropwise to 20 mL of 25% tetrabutyl titanate solution, and stirred vigorously for 10 min at a stirring speed of 550 r / min to obtain a precipitate. The stirring was continued for 1.8 h, and the precipitate was allowed to settle for 11.5 h. The precipitate was washed three times with deionized water to obtain TiO 2 Precursor.

[0033] B2, TiO obtained in B1 2 The precursor was placed in an oven, dried at 70 °C for 1 h, and then calcined in a nitrogen atmosphere at 410 °C for 1 h to obtain nitrogen-doped TiO 2 .

[0034] (2) preparing rice husk ash, the preparation method thereof is as follows:

[0035] C1. Immerse the rice husk in an acid solution with a mass fraction of 2.2% for 1.5 hours, filter it out, wash it with water until it is neutral, and dry it naturally to obtain acid-soaked rice husk.

[0036] C2. Place the acid-soaked rice husk obtained in C1 into a crucible, and then put it into a muffle furnace, calcine it at 620°C for 28 minutes, take it out, and naturally cool it to room temperature to obtain rice husk ash.

[0037] (3) A high temperature resistant battery box is prepared, and the preparation method is as follows:

[0038] S1, by weight, 68 parts of polypropylene, 18 parts of glass fiber, 3.5 parts of conductive flake graphite, and nitrogen-doped TiO 2 4 parts of rice husk ash, 4 parts of rice husk ash, 0.7 parts of lubricant, 12 parts of compatibilizer, 0.3 parts of antioxidant and 0.8 parts of light stabilizer were added into a mixer, the speed was 380r / min, and the mixture was stirred for 6 minutes to obtain a mixture.

[0039] S2. The mixed material obtained in S1 is vacuum dried at a temperature of 70°C and an absolute pressure of 0.02 MPa for 2 h, and then added into a twin-screw extruder for melt extrusion and granulation. The temperature of zone 1 of the twin-screw extruder is 175°C, the temperature of zone 2 is 185°C, the temperature of zone 3 is 180°C, the temperature of zone 4 is 190°C, the temperature of zone 5 is 170°C, the head temperature is 160°C, and the main engine speed is 380 rpm to obtain a composite material.

[0040] S3. The composite material obtained in S2 is injection molded at 220° C., then cooled to room temperature, and demolded to obtain a battery box.

[0041] Among them, the lubricant is calcium stearate, which is purchased from Hebei Qianyou New Materials Technology Co., Ltd. The compatibilizer is polylactic acid grafted cellulose acetate copolymer, specifically PVCSIC3704 cellulose ester polylactic acid grafted copolymer, which is purchased from Qieke New Materials Technology (Shanghai) Co., Ltd. The light stabilizer is 2-(2-hydroxy-3,5-dibutyl tert-phenyl)-5-chlorobenzotriazole (purity 98%), which is purchased from Shanghai Yuanye Biotechnology Co., Ltd. The antioxidant is bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite (purity 99%), which is purchased from Hubei Jusheng Technology Co., Ltd. Polypropylene (K8303) is purchased from Suzhou Zhensu New Materials Co., Ltd. The glass fiber is 3-5mm chopped glass fiber (BLXW-01), which is purchased from Lingshou County Jiashuo Building Materials Processing Co., Ltd. The fixed carbon content of conductive flake graphite (y-066) is ≥98%, the crystal particle size is 3mm, the flake size is 2mm, and the moisture content is ≤0.1%. It is purchased from Qingdao Qinglin Graphite Co., Ltd.

[0042] Example 2: The difference between this example and Example 1 is that: (1) Preparation of nitrogen-doped TiO 2 , and its preparation method is as follows:

[0043] B1. At room temperature, 10 mL of 25% ammonia water was added dropwise to 20 mL of 25% tetrabutyl titanate solution, and stirred vigorously for 12 min at a stirring speed of 500 r / min to obtain a precipitate. The stirring was continued for 2 h, and the precipitate was allowed to settle for 12 h. The precipitate was washed three times with deionized water to obtain TiO 2 Precursor.

[0044] B2, TiO obtained in B1 2 The precursor was placed in an oven, dried at 60 °C for 1 h, and then calcined in a nitrogen atmosphere at 400 °C for 1 h to obtain nitrogen-doped TiO 2 .

[0045] Example 3: The difference between this example and Example 1 is that: (1) Preparation of nitrogen-doped TiO 2 , and its preparation method is as follows:

[0046] B1. At room temperature, 10 mL of 25% ammonia water was added dropwise to 20 mL of 25% tetrabutyl titanate solution, and stirred vigorously for 9 min at a stirring speed of 600 r / min to obtain a precipitate. The stirring was then continued for 1.5 h, and the precipitate was allowed to settle for 11 h. The precipitate was washed three times with deionized water to obtain TiO 2 Precursor.

[0047] B2, TiO obtained in B1 2 The precursor was placed in an oven, dried at 80 °C for 1 h, and then calcined in a nitrogen atmosphere at 420 °C for 1 h to obtain nitrogen-doped TiO 2 .

[0048] Example 4: The difference between this example and Example 1 is that: (2) rice husk ash is prepared, and the preparation method thereof is as follows:

[0049] C1. Immerse the rice husk in an acid solution with a mass fraction of 2% for 2 hours, filter it out, wash it with water until it is neutral, and dry it naturally to obtain acid-soaked rice husk.

[0050] C2. Place the acid-soaked rice husk obtained in C1 into a crucible, and then put it into a muffle furnace, calcine it at 600°C for 30 minutes, take it out, and cool it naturally to room temperature to obtain rice husk ash.

[0051] Example 5: The difference between this example and Example 1 is that: (2) rice husk ash is prepared, and the preparation method thereof is as follows:

[0052] C1. Immerse the rice husk in an acid solution with a mass fraction of 2.5% for 1 hour, filter it out, wash it with water until it is neutral, and dry it naturally to obtain acid-soaked rice husk.

[0053] C2. Place the acid-soaked rice husk obtained in C1 into a crucible, and then put it into a muffle furnace, calcine it at 640°C for 25 minutes, take it out, and naturally cool it to room temperature to obtain rice husk ash.

[0054] Embodiment 6: The difference between this embodiment and embodiment 1 is that: (3) a high temperature resistant battery box is prepared, and the preparation method thereof is as follows:

[0055] S1, by weight, 65 parts of polypropylene, 17 parts of glass fiber, 3 parts of conductive flake graphite, and nitrogen-doped TiO 2 3 parts of sesame, 3 parts of rice husk ash, 0.6 parts of lubricant, 11 parts of compatibilizer, 0.2 parts of antioxidant and 0.7 parts of light stabilizer were added into a mixer, the speed was 350r / min, and the mixture was stirred for 8 minutes to obtain a mixture.

[0056] S2. The mixed material obtained in S1 is vacuum dried at a temperature of 70°C and an absolute pressure of 0.02 MPa for 2 h, and then added into a twin-screw extruder for melt extrusion and granulation. The temperature of zone 1 of the twin-screw extruder is 175°C, the temperature of zone 2 is 185°C, the temperature of zone 3 is 180°C, the temperature of zone 4 is 190°C, the temperature of zone 5 is 170°C, the head temperature is 160°C, and the main engine speed is 380 rpm to obtain a composite material.

[0057] S3. The composite material obtained in S2 is injection molded at 220° C., then cooled to room temperature, and demolded to obtain a battery box.

[0058] Embodiment 7: The difference between this embodiment and embodiment 1 is that: (3) a high temperature resistant battery box is prepared, and the preparation method thereof is as follows:

[0059] S1, by weight, 70 parts of polypropylene, 20 parts of glass fiber, 4 parts of conductive flake graphite, and nitrogen-doped TiO 2 5 parts of sesame, 5 parts of rice husk ash, 0.8 parts of lubricant, 14 parts of compatibilizer, 0.6 parts of antioxidant and 1 part of light stabilizer were added into a mixer, the speed was 400r / min, and the mixture was stirred for 5 minutes to obtain a mixture.

[0060] S2. The mixed material obtained in S1 is vacuum dried at a temperature of 70°C and an absolute pressure of 0.02 MPa for 2 h, and then added into a twin-screw extruder for melt extrusion and granulation. The temperature of zone 1 of the twin-screw extruder is 175°C, the temperature of zone 2 is 185°C, the temperature of zone 3 is 180°C, the temperature of zone 4 is 190°C, the temperature of zone 5 is 170°C, the head temperature is 160°C, and the main engine speed is 380 rpm to obtain a composite material.

[0061] S3. The composite material obtained in S2 is injection molded at 220° C., then cooled to room temperature, and demolded to obtain a battery box.

[0062] Comparative Example 1: The difference between this comparative example and Example 1 is that the nitrogen-doped TiO 2 and rice husk ash.

[0063] Specifically, a high temperature resistant battery box is prepared, and the preparation method thereof is as follows:

[0064] S1. Add 68 parts of polypropylene, 18 parts of glass fiber, 3.5 parts of conductive flake graphite, 0.7 parts of lubricant, 12 parts of compatibilizer, 0.3 parts of antioxidant and 0.8 parts of light stabilizer into a mixer by weight, rotate at 380 r / min, stir and mix for 6 minutes to obtain a mixture.

[0065] S2. The mixed material obtained in S1 is vacuum dried at a temperature of 70°C and an absolute pressure of 0.02 MPa for 2 h, and then added into a twin-screw extruder for melt extrusion and granulation. The temperature of zone 1 of the twin-screw extruder is 175°C, the temperature of zone 2 is 185°C, the temperature of zone 3 is 180°C, the temperature of zone 4 is 190°C, the temperature of zone 5 is 170°C, the head temperature is 160°C, and the main engine speed is 380 rpm to obtain a composite material.

[0066] S3. The composite material obtained in S2 is injection molded at 220° C., then cooled to room temperature, and demolded to obtain a battery box.

[0067] Comparative Example 2: The difference between this comparative example and Example 1 is that the nitrogen-doped TiO 2 .

[0068] Specifically, a high temperature resistant battery box is prepared, and the preparation method thereof is as follows:

[0069] S1. Add 68 parts of polypropylene, 18 parts of glass fiber, 3.5 parts of conductive flake graphite, 4 parts of rice husk ash, 0.7 parts of lubricant, 12 parts of compatibilizer, 0.3 parts of antioxidant and 0.8 parts of light stabilizer into a mixer at a speed of 380 r / min and stir for 6 minutes to obtain a mixture.

[0070] S2. The mixed material obtained in S1 is vacuum dried at a temperature of 70°C and an absolute pressure of 0.02 MPa for 2 h, and then added into a twin-screw extruder for melt extrusion and granulation. The temperature of zone 1 of the twin-screw extruder is 175°C, the temperature of zone 2 is 185°C, the temperature of zone 3 is 180°C, the temperature of zone 4 is 190°C, the temperature of zone 5 is 170°C, the head temperature is 160°C, and the main engine speed is 380 rpm to obtain a composite material.

[0071] S3. The composite material obtained in S2 is injection molded at 220° C., then cooled to room temperature, and demolded to obtain a battery box.

[0072] Comparative Example 3: This comparative example differs from Example 1 in that rice husk ash is deleted.

[0073] Specifically, a high temperature resistant battery box is prepared, and the preparation method thereof is as follows:

[0074] S1, by weight, 68 parts of polypropylene, 18 parts of glass fiber, 3.5 parts of conductive flake graphite, and nitrogen-doped TiO 2 4 parts of propylene glycol, 0.7 parts of lubricant, 12 parts of compatibilizer, 0.3 parts of antioxidant and 0.8 parts of light stabilizer were added into a mixer, the speed was 380 r / min, and the mixture was stirred for 6 minutes to obtain a mixture.

[0075] S2. The mixed material obtained in S1 is vacuum dried at a temperature of 70°C and an absolute pressure of 0.02 MPa for 2 h, and then added into a twin-screw extruder for melt extrusion and granulation. The temperature of zone 1 of the twin-screw extruder is 175°C, the temperature of zone 2 is 185°C, the temperature of zone 3 is 180°C, the temperature of zone 4 is 190°C, the temperature of zone 5 is 170°C, the head temperature is 160°C, and the main engine speed is 380 rpm to obtain a composite material.

[0076] S3. The composite material obtained in S2 is injection molded at 220° C., then cooled to room temperature, and demolded to obtain a battery box.

[0077] Comparative Example 4: The difference between this comparative example and Example 1 is that rice husk ash is deleted and nitrogen-doped TiO 2 Replaced with nano-TiO 2 .

[0078] Specifically, a high temperature resistant battery box is prepared, and the preparation method thereof is as follows:

[0079] S1. By weight, 68 parts of polypropylene, 18 parts of glass fiber, 3.5 parts of conductive flake graphite, and nano-TiO 2 4 parts of propylene glycol, 0.7 parts of lubricant, 12 parts of compatibilizer, 0.3 parts of antioxidant and 0.8 parts of light stabilizer were added into a mixer, the speed was 380 r / min, and the mixture was stirred for 6 minutes to obtain a mixture.

[0080] S2. The mixed material obtained in S1 is vacuum dried at a temperature of 70°C and an absolute pressure of 0.02 MPa for 2 h, and then added into a twin-screw extruder for melt extrusion and granulation. The temperature of zone 1 of the twin-screw extruder is 175°C, the temperature of zone 2 is 185°C, the temperature of zone 3 is 180°C, the temperature of zone 4 is 190°C, the temperature of zone 5 is 170°C, the head temperature is 160°C, and the main engine speed is 380 rpm to obtain a composite material.

[0081] S3. The composite material obtained in S2 is injection molded at 220° C., then cooled to room temperature, and demolded to obtain a battery box.

[0082] Comparative Example 5: The difference between this comparative example and Example 1 is that nitrogen-doped TiO 2 Replaced with nano-TiO 2 .

[0083] Specifically, a high temperature resistant battery box is prepared, and the preparation method thereof is as follows:

[0084] S1. By weight, 68 parts of polypropylene, 18 parts of glass fiber, 3.5 parts of conductive flake graphite, and nano-TiO 2 4 parts of rice husk ash, 4 parts of rice husk ash, 0.7 parts of lubricant, 12 parts of compatibilizer, 0.3 parts of antioxidant and 0.8 parts of light stabilizer were added into a mixer, the speed was 380r / min, and the mixture was stirred for 6 minutes to obtain a mixture.

[0085] S2. The mixed material obtained in S1 is vacuum dried at a temperature of 70°C and an absolute pressure of 0.02 MPa for 2 h, and then added into a twin-screw extruder for melt extrusion and granulation. The temperature of zone 1 of the twin-screw extruder is 175°C, the temperature of zone 2 is 185°C, the temperature of zone 3 is 180°C, the temperature of zone 4 is 190°C, the temperature of zone 5 is 170°C, the head temperature is 160°C, and the main engine speed is 380 rpm to obtain a composite material.

[0086] S3. The composite material obtained in S2 is injection molded at 220° C., then cooled to room temperature, and demolded to obtain a battery box.

[0087] Test example: Test object: Composite materials were prepared according to Example 1 to Example 7 and Comparative Example 1 to Comparative Example 5.

[0088] Test method and content: Refer to GB / T 1040.2-2006 to test the tensile strength T of each test object 0 And the tensile strength T of each test object after high temperature treatment n , and calculate the tensile strength retention rate △T of each test object after high temperature treatment. △T=T n / T 0 ×100%. The high temperature treatment condition is 120℃×7d. The larger the △T value, the stronger the high temperature resistance of the corresponding test object.

[0089] Test results: See Table 1.

[0090] Table 1. Test data of the experimental example

[0091] Tensile strength / MPa Retention rate / % Example 1 44.8 91.9 Example 2 44.7 92.0 Example 3 45.2 92.4 Example 4 44.7 91.6 Example 5 44.4 91.5 Example 6 45.2 92.1 Example 7 45.1 92.1 Comparative Example 1 39.8 83.6 Comparative Example 2 42.1 86.5 Comparative Example 3 41.0 86.9 Comparative Example 4 39.5 84.1 Comparative Example 5 42.5 87.1

[0092] Result analysis: Analyze Example 1-Example 7 and combine the data in Table 1 and Figure 1-Figure 2It can be seen that the tensile strength test data of the composite material prepared by the present invention is as high as 44.4MPa or more, and the tensile strength retention rate after 120℃×7d high temperature treatment is higher than 91.5%. This shows that the composite material / battery box prepared by the present invention has high tensile strength and excellent high temperature resistance.

[0093] Analyze Example 1 and Comparative Examples 1-5 and combine the data in Table 1 and Figure 1-Figure 2 By comparing Comparative Example 1 with Comparative Example 2, it can be seen that the addition of rice husk ash can improve the tensile strength and high temperature resistance of the composite material / battery box. By comparing Comparative Example 1 with Comparative Example 3, it can be seen that nitrogen-doped TiO 2 The addition of can also improve the tensile strength and high temperature resistance of the composite material / battery box. 2 A synergistic effect can be produced to synergistically improve the tensile strength and high temperature resistance of the composite material / battery box.

[0094] Combining Comparative Example 4 with Comparative Example 5, it can be seen that nano-TiO 2 The tensile strength of the composite material will be slightly reduced due to the sufficient amount of nano-TiO 2 The nano-TiO 2 There is no obvious synergistic effect between itself and rice husk ash, and it is impossible to synergistically improve the tensile strength and high temperature resistance of the composite material / battery box.

[0095] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0096] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A high temperature resistant battery box, characterized in that: The invention comprises the following components by weight: 65-70 parts of polypropylene, 17-20 parts of glass fiber, 3-4 parts of conductive flake graphite, 3-5 parts of nitrogen-doped TiO2, 3-5 parts of rice husk ash, 0.6-0.8 parts of lubricant, 11-14 parts of compatibilizer, 0.2-0.6 parts of antioxidant and 0.7-1 parts of light stabilizer.

2. The high temperature resistant battery box according to claim 1, characterized in that: The preparation method of the nitrogen-doped TiO2 is as follows: B1. At room temperature, add 10 mL of 25% ammonia water dropwise to 20 mL of 25% tetrabutyl titanate solution, stir until a precipitate is obtained, then continue stirring for 1.5-2 hours, and then let the precipitate settle for 11-12 hours. The precipitate after settling is washed three times with deionized water to obtain a TiO2 precursor; B2. Place the TiO2 precursor obtained in B1 into an oven, dry it at 60-80°C for 1 hour, and then calcine it in a nitrogen atmosphere at 400-420°C for 1 hour to obtain nitrogen-doped TiO2.

3. The high temperature resistant battery box according to claim 2, characterized in that: In B1, the stirring speed is 500-600 r / min.

4. The high temperature resistant battery box according to claim 1, characterized in that: The preparation method of the rice husk ash is as follows: C1. Immerse the rice husk in an acid solution with a mass fraction of 2-2.5% for 1-2 hours, filter out, wash with water until neutral, and dry naturally to obtain acid-soaked rice husk; C2. Place the acid-soaked rice husk obtained in C1 into a crucible, and then into a muffle furnace, calcine at 600-640°C for 25-30 minutes, take out, and naturally cool to room temperature to obtain rice husk ash.

5. The high temperature resistant battery box according to claim 1, characterized in that: The lubricant is calcium stearate or polyethylene wax.

6. The high temperature resistant battery box according to claim 1, characterized in that: The compatibilizer is a polylactic acid grafted cellulose acetate copolymer.

7. The high temperature resistant battery box according to claim 1, characterized in that: The light stabilizer is 2-(2-hydroxy-3,5-dibutyl-tert-phenyl)-5-chlorobenzotriazole.

8. The high temperature resistant battery box according to claim 1, characterized in that: The antioxidant is bis(2,4-di-tert-butylphenyl)pentaerythritol diphosphite.

9. A method for preparing a high temperature resistant battery box according to any one of claims 1 to 8, characterized in that: The steps include: S1. Add polypropylene, glass fiber, conductive flake graphite, nitrogen-doped TiO2, rice husk ash, lubricant, compatibilizer, antioxidant and light stabilizer into a mixer at a speed of 350-400 r / min, and stir and mix for 5-8 min to obtain a mixture; S2, the mixed material obtained in S1 was vacuum dried at a temperature of 70°C and an absolute pressure of 0.02MPa for 2h, and then added into a twin-screw extruder for melt extrusion granulation, wherein the temperature of the first zone of the twin-screw extruder was 175°C, the temperature of the second zone was 185°C, the temperature of the third zone was 180°C, the temperature of the fourth zone was 190°C, the temperature of the fifth zone was 170°C, the head temperature was 160°C, and the main engine speed was 380rpm, to obtain a composite material; S3. The composite material obtained in S2 is injection molded at 210-230°C, then cooled to room temperature, and demolded to obtain a battery box.

Citation Information

Patent Citations

  • Rice hull ash modified ABS composite material and preparation method thereof

    CN104845023A

  • Long-glass fiber-modified polypropylene for instrument panel skeleton

    CN107141596A

  • High-performance conductive polypropylene composite material and preparation method thereof

    CN108192207A

  • Rice hull ash and preparation method thereof, rice hull ash geopolymer and preparation method thereof

    CN111995272A

  • Biomaterial Composite

    US20170121493A1